Short-term effects of ambient air pollutants and meteorological factors on emergency department visits in tropical Haikou, China - Jichao Peng; Xinxin Wu; Jun Chen; Jin Qian; Nan Li; Yang Yi; Yue Huang; Juncai Lu; Wenxing Zhang; Zhengyu Li; Zhao Li; Min Li; et al. (Scientific Reports)
Abstract Exposure to atmospheric pollutants and meteorological factors is closely linked to human health risks, however, studies in tropical regions remain limited. Assessment of the associations between air pollutants, meteorological factors, and all-cause emergency department visits in Haikou City was conducted to validate the generalizability of previous findings and uncover novel environment-health linkages. We analyzed 1,041,760 ED visits from January 1, 2018, to December 31, 2021, using a distributed lag non-linear model to assess environmental factors’ health effects and lagged impacts with subgroup analyses stratified by gender and age. Additionally, four sensitivity analyses were conducted to verify the robustness of the findings. The results demonstrated significant nonlinear associations between meteorological factors, air pollutants, and emergency department visit risks in Haikou City. PM₂.₅ and PM₁₀ showed nonsignificant effect magnitudes, while temperature (12–25 °C) and relative humidity (80–85%) exhibited protective effects. Low-concentration SO₂ (< 15 µg/m³) and CO (< 0.5 mg/m³) exposures significantly elevated visit risks, whereas high-concentration NO₂ (> 30 µg/m³) exposure displayed hazardous effects. Stratified analyses revealed: that elevated temperatures disproportionately affected males and children; humidity above 80% conferred protection on males and individuals younger than 34 years; elderly males exhibited heightened sensitivity to O₃ and NO₂ exposures; female children faced increased risks from low-concentration CO exposure, and females aged 15–34 showed specific responses to SO₂ exposure. In the tropical coastal city, PM2.5 and PM10 exhibited no significant associations with all-cause emergency risks, while low-level concentrations of SO2 and CO demonstrated specific effects. Although pandemic measures modified certain exposure scenarios, the core mechanisms underlying environment-health associations remained fundamentally unaltered. These findings provide references for revising air quality standards in tropical coastal regions, suggest incorporating SO₂/CO into health warning systems, and propose a climate-pollution co-regulation paradigm for global cities with similar environmental profiles.